2022
DOI: 10.4049/immunohorizons.2100072
|View full text |Cite
|
Sign up to set email alerts
|

Expression Levels of Lamin A or C Are Critical to Nuclear Maturation, Functional Responses, and Gene Expression Profiles in Differentiating Mouse Neutrophils

Abstract: Neutrophils mediate critical innate immune responses by migrating to sites of infection or inflammation, phagocytosing microorganisms, and releasing an arsenal of antimicrobial agents, including reactive oxygen species. These functions are shared by other innate immune cell types, but an interesting feature of neutrophils is their hallmark lobulated nuclei. Although why this bizarre nuclear shape forms is still being elucidated, studies of two intermediate filament proteins that associate with the nuclear enve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…To emphasize more over the dual aspects of NF‐κB mediated transcription deregulation in cases of loss of functional lamin A, studies have linked downregulated NF‐κB expression to the observed loss of gp91(phox) expression, which may also have effects on chemokine or cytokine‐mediated signal transduction or associated signaling pathways (Szymczak et al., 2022). So, the altered function of lamin A and ensuing aberrant nuclear organization in DCM may be linked to inflammatory or stress responses triggered by mechanobiology and its impact on the NF‐κB regulatory axis (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…To emphasize more over the dual aspects of NF‐κB mediated transcription deregulation in cases of loss of functional lamin A, studies have linked downregulated NF‐κB expression to the observed loss of gp91(phox) expression, which may also have effects on chemokine or cytokine‐mediated signal transduction or associated signaling pathways (Szymczak et al., 2022). So, the altered function of lamin A and ensuing aberrant nuclear organization in DCM may be linked to inflammatory or stress responses triggered by mechanobiology and its impact on the NF‐κB regulatory axis (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…53 Overexpression of either lamin A or lamin C disrupts neutrophil nuclear morphology and impairs chemotaxis and other functions. 54 Lamin A/C level is also affected by the activation state of leukocytes. Expression of lamin A/C is low in lymphoid cell lines.…”
Section: The Mechanical Properties Of the Nucleusmentioning
confidence: 99%
“…83,84 Down-regulation of lamin A/C is necessary because overexpression of either lamin isoform greatly reduces the number of multilobed nuclei. 54 How LBR mediates nuclear lobulation is unknown. LBR contains an N-terminal nucleoplasmic domain that binds to lamin B, histones, DNA and HP1, and a C-terminal 8-transmembrane domain that functions as a sterol reductase (Figure 2).…”
Section: Nuclear Morphology and Nuclear Lobulationmentioning
confidence: 99%
See 2 more Smart Citations